2007
DOI: 10.1007/s11276-006-0724-8
|View full text |Cite
|
Sign up to set email alerts
|

Relay sensor placement in wireless sensor networks

Abstract: This paper addresses the following relay sensor placement problem: given the set of duty sensors in the plane and the upper bound of the transmission range, compute the minimum number of relay sensors such that the induced topology by all sensors is globally connected. This problem is motivated by practically considering the tradeoff among performance, lifetime, and cost when designing sensor networks. In our study, this problem is modelled by a NP-hard network optimization problem named Steiner Minimum Tree w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
309
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 412 publications
(312 citation statements)
references
References 21 publications
3
309
0
Order By: Relevance
“…Generally, throwboxes are less effective in reducing message delay under single path routing than under multi-path routing. (Case 7,8,9) We now consider the case of epidemic routing. Epidemic routing does not utilize any information about the network.…”
Section: Single Path Routingmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, throwboxes are less effective in reducing message delay under single path routing than under multi-path routing. (Case 7,8,9) We now consider the case of epidemic routing. Epidemic routing does not utilize any information about the network.…”
Section: Single Path Routingmentioning
confidence: 99%
“…The node placement problem has been studied in wireless [20] and sensor networks [8], [19]. In [20], the authors study the placement of access points to form a mesh network for Internet traffic and proposes greedy algorithms.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [11] demonstrated that the algorithm proposed in [10] is in fact a 4-approximation algorithm, and proposed a 3-approximation algorithm for the RNP problem. Cheng et al [12] presented a 3-approximation algorithm and a 2.5-approximation algorithm based on so-called 3-star structure. Misra et al [13,14] studied the constrained RNP problem, in which RNs can only be placed at the predetermined locations, in singletiered WSNs and proposed a polynomial time O(1)-approximation algorithm.…”
Section: Single-tiered Rnp Problemmentioning
confidence: 99%
“…However, different from the RNP problem that has been extensively studied [8][9][10][11][12][13][14][15][16][17][18][19][20], the works on the DCRNP problem are very limited [21][22][23][24][25]. Moreover, published works only concentrate on the DCRNP problem in single-tiered WSNs.…”
Section: Introductionmentioning
confidence: 99%